2015
DOI: 10.1002/jwmg.869
|View full text |Cite
|
Sign up to set email alerts
|

Resource separation by mountain ungulates on a landscape modified by fire

Abstract: Fire restructures plant communities and can be an important modifier of ecosystems. Increases in forage quantity and quality in burned areas attract large ungulates, and may result in changes to animal distributions. In mountainous northern British Columbia where prescribed fire is used to enhance ungulate range, there is concern that expanding elk (Cervus elaphus) populations will move in response to burning into the traditional ranges of another grazing species, Stone's sheep (Ovis dalli stonei), and have ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…The AIC score identifies the most parsimonious model, which has the fewest variables explaining the greatest amount of variation (Thompson and Lee 2000). We ranked models using the difference in AIC between the model of interest and the model with the smallest AIC (DAIC; Anderson et al 2000, Burnham andAnderson 2002) and calculated Akaike weights (w i ; Burnham and Anderson 2002) to identify a suite of competing models (Sittler et al 2015). We defined competing models as all those required for Sw i to be >0.95 because the best model identified with an AIC approach is not necessarily representative of landscape use (Sittler et al 2015).…”
Section: Resource Selection Model Developmentmentioning
confidence: 99%
“…The AIC score identifies the most parsimonious model, which has the fewest variables explaining the greatest amount of variation (Thompson and Lee 2000). We ranked models using the difference in AIC between the model of interest and the model with the smallest AIC (DAIC; Anderson et al 2000, Burnham andAnderson 2002) and calculated Akaike weights (w i ; Burnham and Anderson 2002) to identify a suite of competing models (Sittler et al 2015). We defined competing models as all those required for Sw i to be >0.95 because the best model identified with an AIC approach is not necessarily representative of landscape use (Sittler et al 2015).…”
Section: Resource Selection Model Developmentmentioning
confidence: 99%
“…Translocations replicate natural migrations from population sources to sinks, but the dearth of source and sink populations, and reduced capacity for migration, is invariably limited by the forced boundaries of the protected area itself. Even behavioural alterations and population redistributions within protected areas are management substitutes for natural stochastic processes that have been suppressed, such as fire [111][112][113], and fear responses lost when humans removed natural predators, or made human disturbance a refuge from predators [29].…”
Section: Discussionmentioning
confidence: 99%
“…Modeling of populations of Asiatic wild ass (Equus hemionus), based on 16 years of previous climate data for Makhtesh Ramon Nature Reserve, Israel, found that in a global change scenario, population fluctuations increased 30%, and extinction rate increased 10 fold [117]. As climate change increases the stochasticity of environmental conditions such as precipitation and fire [113,118], large herbivore management in the future will have to become more proactive and predictive of future change, rather than relying on reactivity to observed changes.…”
Section: Discussionmentioning
confidence: 99%
“…Most cover types were open enough to easily see and count ungulates, and we assumed our repeated samples of locations were representative of population response. The aerial survey sample corresponds with data obtained from a relatively few global positioning system (GPS)‐collared elk and Stone's sheep in the study area (Sittler et al ). Animal occurrences obtained using repeated systematic aerial surveys conducted under good weather conditions can provide accurate information on habitat use (Potvin et al ).…”
Section: Methodsmentioning
confidence: 99%
“…As elk move on burned slopes into the small traditional ranges of Stone's sheep, there is concern about potential forage competition between the 2 species and displacement of Stone's sheep. Higher elk numbers also could increase predation risk for Stone's sheep by facilitating the increase of shared predators (Sittler et al ).…”
mentioning
confidence: 99%